A study on the impact of CSR performance on the financial performance of Indian service sector. (2018) - Kaur, Sukhpreet
Corporate social responsibility (CSR) initiatives performed and the impact of corporate social responsibility scores on the financial performance of the Indian service sector, i.e., IT, banking and telecom is found through content analysis, regression analysis and ANOVA techniques. It is found that 'promotion of education' is the maximum performed (CSR score 71) and 'contribution to Prime Minister's relief fund' is the least performed CSR activity (CSR score 24) of Indian service sector. Significant positive relationship is found between the CSR score and the net worth of companies. CSR is found to be a true reflector of net worth of the Indian service sector. There is no significant difference in the CSR performance of all the three areas but more inconsistency in the performance is found in the Indian banking sector. The study gives an implication that CSR can be considered as a major area of concern to improve the financial performance of Indian service sector.